Hukum Penggunaan Destilasi Tetes Tebu (Rum) sebagai Campuran Makanan Menurut Fikih Islam - Ummu Kalsum; Akhmad Hanafi Dain Yunta; Sirajuddin Sirajuddin (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2023)
This study aims to determine the law of consuming food that uses a mixture of rum. The problem that the authors raise in this study is how the view of Islamic law regarding the use of rum as a mixture of food ingredients. This research is a qualitative descriptive research (non-statistical), which focuses on the study of manuscripts and texts, using a normative juridical approach. The results of this study indicate that the law of using rum to mix food is unlawful, both uncooked and after cooked. Even if the mixture of rum in the cake or food is small, it is still considered unlawful. Because this means consuming a small amount of khamr and rum is an intoxication. The alcohol content in rum reaches 33.4%, including class C in the division of liquor.